2022
DOI: 10.3389/fpain.2021.810809
|View full text |Cite
|
Sign up to set email alerts
|

Small Fiber Polyneuropathy May Be a Nexus Between Autonomic Nervous System Dysregulation and Pain in Interstitial Cystitis/Bladder Pain Syndrome

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a highly heterogeneous chronic and debilitating condition which effects millions of women and men in the United States. While primarily defined by urinary symptoms and pain perceived to be emanating from the bladder, IC/BPS patients frequently have co-occurring conditions and symptoms, many of which affect diverse body systems related to autonomic nervous system function. The impact on the autonomic system appears to stem from increased sympathetic innerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…27 Isolated SFPN is commonly associated with dysfunction of the autonomic nervous system, 8 and patients with FM and findings of SFPN n ORIGINAL RESEARCH Small-Fiber Polyneuropathy and IC/BPS have more microvascular autonomic symptoms than those without. 28 We have previously suggested that SFPN may be contributing to the subtle autonomic system abnormalities found in patients with IC/BPS, 29 and this association and potential etiologic link require further research.…”
Section: Discussionmentioning
confidence: 99%
“…27 Isolated SFPN is commonly associated with dysfunction of the autonomic nervous system, 8 and patients with FM and findings of SFPN n ORIGINAL RESEARCH Small-Fiber Polyneuropathy and IC/BPS have more microvascular autonomic symptoms than those without. 28 We have previously suggested that SFPN may be contributing to the subtle autonomic system abnormalities found in patients with IC/BPS, 29 and this association and potential etiologic link require further research.…”
Section: Discussionmentioning
confidence: 99%